O impacto da pré-tarefa no desempenho oral e escrito de alunos em tarefas comunicativas em inglês a partir de uma proposta de aprendizagem colaborativa - Goulart, Fernanda (2025)
The main objective of this doctoral research was to evaluate the impact of pre-task activities on students’ oral and written performance when engaged in communicative tasks in English, within the context of a Thematic Task-Based Language Teaching framework. To this end, a methodological proposal for the pre-task phase was developed, emphasizing the construction of language learning through the creation of a collaborative environment fostered by interaction between teacher and students, as well as among students themselves. The theoretical foundations of the pre-task phase are grounded in studies on interaction and collaboration in foreign language teaching (Allwright, 1984; Almeida Filho; Barbirato, 2016; Figueiredo, 2019), along with the notions of meaning negotiation and reactive focus on form (Long, 2015, 2016). Vygotsky’s sociocultural theory (1978) supports key concepts such as collaborative learning (Torres; Irala, 2014), knowledge co-construction (Figueiredo, 2019; Swain, 2000), collaborative dialogues (Swain, 2000), and the process of scaffolding (Figueiredo, 2019; Swain; Watanabe, 2013). This investigation was conducted through the implementation of nine task cycles – composed of pre-task, task, and post-task phases – centered around the theme “Cultural Diversity,” which guided the development of didactic materials for an in-person English course offered to 14 students enrolled in two technical high school programs at a Federal Institute located in the interior of São Paulo state, Brazil. This is a qualitative-interpretive study (Moita Lopes, 1994). Data generation instruments included questionnaires, interviews, video recordings of classroom interactions, and the tasks produced by the participants throughout the course. Data analysis was based on the selection and organization of the corpus and the identification of emerging patterns. The results revealed that: (1) the pre-task phase promoted student agency in the learning process, contributing to the joint construction of linguistic knowledge and thematic content; (2) participants positively evaluated the pre-task activities, recognizing their role in generating ideas and learning relevant vocabulary; and (3) the tasks produced by the students showed elements that had been explored during the pre-task phase. It is concluded that the pre-task phase had a positive impact on students’ performance in oral and written communicative tasks. The findings of this study contribute to the advancement of research in task-based language teaching, particularly regarding the role of pre-task activities in promoting meaningful and collaborative target language learning within the framework of a Thematic Task-Based Language Teaching approach.